If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.66x + -5 = 2x Reorder the terms: -5 + 0.66x = 2x Solving -5 + 0.66x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + 0.66x + -2x = 2x + -2x Combine like terms: 0.66x + -2x = -1.34x -5 + -1.34x = 2x + -2x Combine like terms: 2x + -2x = 0 -5 + -1.34x = 0 Add '5' to each side of the equation. -5 + 5 + -1.34x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1.34x = 0 + 5 -1.34x = 0 + 5 Combine like terms: 0 + 5 = 5 -1.34x = 5 Divide each side by '-1.34'. x = -3.731343284 Simplifying x = -3.731343284
| 3(x-4)=-4+44 | | 15+3n=27 | | -6=-4-2x | | -8x(x+1)=4(x-11) | | 4x+1=5j-1 | | y=x^2+60x-300 | | 4(3+3x)-2=70 | | x+(x+5)=69 | | 22x=25x-6 | | 6(2n-1)=2(5n-3)+4n | | 9y+1=8y-2 | | (u-7)(u+1)= | | 3(a-5)+7=-2 | | 3x^2-21x-36=0 | | -3(6-2t)=-48 | | 8z^2+20z-49=0 | | 5x+15-2x=25+3x-10 | | 5log(x+3)=12 | | 5x=42-3x | | x^2-6+3x^2-10x+2= | | 6x-1=-2(3-5x) | | 7=(t-1)-2(t-3) | | 9+3x=-(x+7) | | 16-x=4+5x | | h=-4t^2+4t+120 | | x^3+3x^2+2x=2x^2+4x | | 3(x-8)+15=-18 | | -1=-14+5x | | 10x-8=10x+5 | | b=zc+m | | 77r^2+53r-40=0 | | 4(x+5)=3(x-2)-2x+2 |